The Increase of Circulating PD-1- and PD-L1-Expressing Lymphocytes in Endometriosis: Correlation with Clinical and Laboratory Parameters. (25th November 2018) - Walankiewicz, Monika; Grywalska, Ewelina; Polak, Grzegorz; Korona-Glowniak, Izabela; Witt, Elzbieta; Surdacka, Agata; Kotarski, Jan; Rolinski, Jacek
Abstract : The cause of endometriosis remains unknown. However, studies investigating the link between this condition and the immune system revealed several immunological abnormalities focused on cell-mediated immunity. As a major immune checkpoint, programmed cell death protein 1 (PD-1) displays an important inhibitory function in the maintenance of peripheral tolerance. The expression of PD-1 and its ligand (PD-L1) may contribute to continuous T cell activation and development of inflammation and injury of the tissue. To our knowledge, this is the first study evaluating frequencies of PD-1-positive T CD3 + cells (CD4 + and CD8 + ) and B cells (CD19 + ) in patients with endometriosis. Peripheral blood (PB) samples from 25 female patients and 20 healthy age and sex-matched subjects serving as controls were used in the study. Using flow cytometric analysis, we assessed the differences in the frequencies of PD-1-positive T and B lymphocytes in the study group and healthy individuals. Alteration of the PD-1/PD-L1 axis may contribute to the pathogenesis of endometriosis, as patients with advanced disease are characterized by higher frequencies of PD-1-positive T and B cells. Expression of PD-1 and PD-L1 on T and B cells could represent the hallmark of immune system reaction to chronic antigenic exposition in patients with endometriosis.